LasB, ExoS and Nan1 genes as potential predictors of site-specific Pseudomonas aeruginosa pathogenicity in nosocomial isolates - Maii Shams Eldeen; Rabab Elsaid; Hanan Salem; Eman Eisa; Rasha Shalaby (Microbes and Infectious Diseases)
Background: Pseudomonas aeruginosa is an opportunistic pathogen that represents a global public health threat. Immunocompromised hosts and cystic fibrosis patients are primarily susceptible to high morbidity and mortality due to pulmonary tract colonization with mucoid Pseudomonas aeruginosa. Differentially expressed virulence factors govern Pseudomonas aeruginosa pathogenicity in different sites of infection. Therefore, the detection of site-specific virulence genes in Pseudomonas aeruginosa isolates may potentially predict the level of Pseudomonas aeruginosa pathogenicity and the outcome in infected patients. Objectives: This study aims to phenotypically and genotypically characterize nosocomial Pseudomonas aeruginosa isolates from different clinical specimens to determine the frequency of LasB, ExoS and Nan1 virulence genes in the collected isolates relative to the site and severity of Pseudomonas aeruginosa infection using conventional polymerase chain reaction. Methods: The study was carried out on 30 Pseudomonas aeruginosa isolates collected from hospitalized patients who have been diagnosed with respiratory tract, bloodstream or burn infection in Tanta University Hospitals. Pseudomonas aeruginosa isolates were phenotypically characterized using standard microbiology techniques and genotypically characterized using conventional PCR for the detection of LasB, ExoS and Nan1 virulence genes. Results: Both Nan1 and ExoS genes were detected in Pseudomonas aeruginosa isolates from 30% of respiratory and burn infections but they were undetectable in all isolates from bloodstream infections. While, LasB gene was detected in all types of clinical specimens (100% of respiratory specimens, 90% of pus and 90% of blood specimens). A significant correlation was found between the site, severity of infection and the presence of multiple virulence genes. Conclusion: Our study reveals site and severity specific detection of certain Pseudomonas aeruginosa virulence genes which may suggest site and severity specific pathogenesis of certain Pseudomonas aeruginosa strains. Our data also imply that precision targeting of specific virulence factors detected in certain infection sites and/or severity should improve therapeutic outcomes of Pseudomonas aeruginosa infections.